Hepatic neuroendocrine carcinoma in a Japanese macaque (Macaca fuscata). Issue 2 (6th December 2018) - Hirata, Akihiro; Miyamoto, Yoko; Kaneko, Akihisa; Sakai, Hiroki; Yoshizaki, Kyoko; Yanai, Tokuma; Miyabe‐Nishiwaki, Takako; Suzuki, Juri
Abstract: Primary neuroendocrine neoplasm of the liver is extremely rare in both humans and non‐human primates. The present report describes the clinical and pathological findings of an aged Japanese macaque ( Macaca fuscata ) with hepatic neuroendocrine carcinoma. To our knowledge, this is the first report of hepatic neuroendocrine neoplasm in macaques.